Construction of Binary Vector With Wound Inducible Promoter for HbsAg Expression: Development of Plant-Based Edible Hepatitis B Vaccine from Indonesian Isolate - Suhandono, Sony; Giri-Rachman, Ernawati A.; Zainuddin, Ima M.; Utari, Putri Dwi; Supraba, Apsari; Estiati, Amy (BRIN, 2007)
Hepatitis B is a serious infectious disease in the third world countries including Indonesia. Vaccination is the most effective way to prevent the spread of the disease; therefore the demand for HBV vaccine is high. In order to produce more vaccine at lower cost, transgenic plant can be chosen to express the vaccine with the above criteria. Several researches were successfully producing transgenic plants expressing HBsAg that formed virus-like particles and induced immune response in human. However, HBsAg expression in transgenic plant needs to be improved especially on gene expression control system. Here, we describe the construction of HBsAg structural gene under the control of wound inducible promoter, MeEF1 promoter from Manihot esculenta Crantz. The HBsAg gene was amplified using PCR from HBV genome isolated from an Indonesian patient. The gene was subsequently fused with VSPaS signal peptide, which targeted the reticulum endoplasm of plant cell. The construct was cloned into binary expression vector for Agrobacterium plant transformation in near future.